Subjective and Neural Responses to Intravenous Alcohol in Young Adults with Light and Heavy Drinking Patterns - Gilman, Jodi M; Ramchandani, Vijay A; Crouss, Tess; Hommer, Daniel W (Neuropsychopharmacology (New York, N.Y.), 2012)
Heavy alcohol consumption during young adulthood is a risk factor for the development of serious alcohol use disorders. Research has shown that individual differences in subjective responses to alcohol may affect individuals’ vulnerability to developing alcoholism. Studies comparing the subjective and objective response to alcohol between light and heavy drinkers (HDs), however, have yielded inconsistent results, and neural responses to alcohol in these groups have not been characterized. We performed a double-blind, placebo-controlled, randomized crossover alcohol challenge study comparing functional magnetic resonance imaging and subjective response to intravenously administered 6% v/v ethanol to a target blood alcohol concentration of 0.08% or placebo between HDs and social drinkers (SDs). During the imaging, we presented emotional cues in order to measure how emotion modulated the effects of alcohol on the brain's reward circuitry. We found that, at equivalent blood alcohol concentrations, HDs reported lower subjective alcohol effects than SDs. Alcohol significantly activated the nucleus accumbens in SDs, but not in HDs. Self-reported ratings of intoxication correlated with striatal activation, suggesting that activation may reflect subjective experience of intoxication. Fearful faces significantly activated the amygdala in the SDs only, and this activation was attenuated by alcohol. This study shows that HDs not only experience reduced subjective effects of alcohol, but also demonstrate a blunted response to alcohol in the brain's reward system. Our findings indicate that reduced subjective and neural response to alcohol in HDs may be suggestive of either the development of tolerance to alcohol, or of pre-existing decreased sensitivity to alcohol's effects.